the peran strategi pembelajaran dalam menciptakan suasana belajar yang aktif dan menyenangkan di MA Nurul ulum: peran strategi pembelajaran dalam menciptakan suasana belajar yang aktif dan menyenangkan di MA Nurul ulum - M Zaidan Zamzami Nur; Althaf Abbad; Syulthon Maulana (Jurnal Penelitian dan Pendidikan IPS, 2026)
This study investigates the role of instructional strategies in creating an active, engaging, and enjoyable learning environment at MA Nurul Ulum. In the context of modern education, the implementation of effective and innovative teaching strategies is crucial for motivating students and improving the overall quality of learning. This study aims to identify the types of strategies used by teachers and analyze their impact on student participation, interaction patterns, and classroom dynamics. Using a qualitative descriptive approach, data were collected through classroom observations, semi-structured interviews with teachers and students, and supporting documentation. The findings indicate that interactive learning methods such as group discussions, project-based learning, collaborative assignments, and multimedia integration  play a significant role in creating a more lively and positive learning environment. These strategies not only increase student engagement but also foster creativity, communication skills, and critical thinking. Furthermore, this study emphasizes that implementing a student-centered approach encourages learners to become more independent, confident, and actively engaged in the learning process. Teachers who consistently vary their teaching techniques are better able to accommodate different learning styles and maintain enthusiasm in the classroom. Overall, this study concludes that the implementation of varied, interactive, and student-focused learning strategies is crucial in creating a more dynamic, meaningful, and enjoyable educational experience at MA Nurul Ulum.